Tuberculosis trends over a five-year period at a tertiary care university-affiliated hospital in Singapore - Jappar, Suzanna Binte (Singapore Med J, 2015)
INTRODUCTION: Tuberculosis (TB), a potentially fatal infectious disease, poses significant health problems. The objective of this study was to analyse trends among newly diagnosed TB patients seen at the Singapore General Hospital (SGH). METHODS: This study was a retrospective case record review of notified TB patients at SGH between 2006 and 2010 (inclusive). RESULTS: A total of 1,979 cases of TB were notified over the five years. The number increased from 368 in 2006 to 407 in 2010 (p = 0.51), in tandem with the increasing number of patients seen at the hospital and the rising population in Singapore. Singaporean residents accounted for 82.8% of the cases, while non-Singaporean residents and non-residents made up the remainder. The year-to-year percentage of non-Singaporean residents and non-residents notified remained stable throughout the five years (p = 0.783). The number of male Singaporean residents (70.7%) notified was more than twice that of female Singaporean residents (29.3%). The majority of patients infected with TB (31.9%) were elderly patients aged > 65 years. Although testing for the human immunodeficiency virus increased from 43.8% (2006) to 64.2% (2010), the number detected with coinfection remained stable (14 and 12 patients in 2006 and 2010, respectively). Mortality rates also remained stable at 12.0%. CONCLUSION: We cannot afford complacency, as there was no downward trend in the number of notified TB cases at SGH from 2006 to 2010. As the elderly contribute significantly to the TB burden, increased efforts are required to manage this vulnerable population.